Finland : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Finland. (IMF Staff Country Reports; Country Report, 2019)
Recent growth has been healthy, and the unemployment rate has fallen to its lowest level since 2011. However, some underlying weaknesses remain. The rate in which new jobs are created and the 'churn' of workers relocating across jobs has not picked up with the recovery, labor productivity growth remains weak, and the outlook for potential growth is constrained by a shrinking workforce. Household debt has been increasing as the economy has recovered, and some borrowers appear vulnerable to interest rate increases.